Analysis of lambda insertions in the fucose utilization region of Escherichia coli K-12: use of lambda fuc and lambda argA transducing bacteriophages to partially order the fucose utilization genes. - Skjold, A C (1982)
Escherichia coli K-12 strains have deletions for the normal lambda integration site were lysogenized with bacteriophage lambda at a site within the L-fucose utilization system (fuc). The frequency of lambda integration at this site is approximately 2 X 10(-8) to 5 X 10(-7). Studies of the lytic properties of these strains indicated very infrequent cell lysis with a relatively low phage burst size. Transductional ability of the phage lysates was found to be normal, comparable to that found in conventional low-frequency transducing lysates. Two major classes of transducing phage were found. One carried the markers argA and fucA (a fucose utilization gene of unknown function previously referred to as fuc-1) and the gene for D-arabinose utilization (dar+). The other carried only fucC, the gene specifying L-fuculose-1-phosphate aldolase. A minor class of phage was found that carried fucA, but not argA or dar+. Upon consideration of the transductional nature of these phage classes, we are proposing that the gene order for the L-fucose utilization system is dar, fucA, (lambda), fucC.